Lung Disease Detection using Radiography Imagery: Comparison between some traditional Machine Learning methods and Inception v3 Convolutional Neural Network - Picasso, Sofía Carmen; Santos, Juan Miguel; Ramele, Rodrigo; Gambini, María Juliana (., 2023)
.
Keywords: Ciencias naturales::Informática y Ciencias de la Información::Ciencias de la computación